Optimalisasi Content Marketing Melalui Video Interaktif Pada Platform E-commerce Untuk Meningkatkan Brand Activation Produk pada PT Lima Benua Koneksindo - Leyla Garida Naribrata; Sugito Sugito (Masyarakat Ekonomi Syariah Bogor, 2026)
The intense competition in the e-commerce industry drives repeated exposure to homogeneous marketing content, triggering content fatigue and reducing consumer engagement. This study aims to analyze the optimization of content marketing through interactive video in increasing product brand activation at PT Lima Benua Koneksindo on e-commerce platforms. The research method applied is a causal quantitative approach. Sampling utilized a census technique (saturated sampling) by involving all internal employees of PT Lima Benua Koneksindo, totaling 20 respondents as expert practitioners who understand the company's business operations. Primary data were collected through structured questionnaires based on Google Forms, while data analysis used Simple Linear Regression techniques assisted by statistical software. The results showed that content marketing through interactive video has a positive and significant effect on product brand activation (t-count= 5.642; Sig. = 0.000 < 0.05). The Coefficient of Determination (R2) value of 0.639 indicates that interactive video can explain 63.9% of the variation in brand activation improvement. Interactivity elements such as shoppable tags, quizzes, and virtual feature simulations are proven effective in transforming passive viewers into active participants, extending page visit duration (dwell time), and bringing brand values to life in real-time. This study suggests management optimize investment in interactive visual production tools to maintain competitiveness in the digital market.